Clinical Study on Patients with Grossly Elevated Erythrocyte Sedimentation Rate - Haque, Md Zahirul; Alam, Saki Md Jakiul; Noman, Mesbahuddin; Azhar, MA (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> This study was done in medicine indoor department of Rajshahi Medical College Hospital from January 2004 to March 2004. Consecutive 100 patients, who were advised to test the ESR by their physicians for their complaints and found to have an ESR, equal to or more than 100 mm in 1st hour, were included in this study. Among 100 patients 56 were male and 44 were female. All of them were classified in five age groups. They were also categorized according to their monthly income and occupation. Fever, generalized weakness, weight loss, pallor, pain, body ache were the common presenting complaints. Haematological disorder appeared to be most common cause (41%) of marked ESR elevation; followed by infectious diseases (36%) and connective tissue disorders (17%). Among the all patients 30% cases were haematological malignancies (i.e. acute myeloblastic and lymphoblastic leukaemia, lymphomas, multiple myeloma). In 4% cases the cause could not be elicited. Â Â  DOI = 10.3329/jom.v8i2.1411 J MEDICINE 2007; 8 : 64-68